1997
DOI: 10.1046/j.1365-2141.1997.1372951.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in culture pH affect the cloning efficiency and differentiation of progenitor cells in ex vivo haemopoiesis

Abstract: Summary.Haemopoietic cultures may experience pH variations of as much as 0·5 units depending on culture duration and cell density. Since pH is a potent modulator of cellular proliferation and differentiation, we examined its effects on the performance of both semisolid and liquid haemopoietic cultures. Culture pH was found to have substantial effects both on progenitor cloning efficiency (as measured in liquid cultures) and on progenitor cell differentiation (as measured in methylcellulose cultures). Liquid cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 15 publications
3
38
2
Order By: Relevance
“…Functional AE1 mediates the Cl À /HCO 3 À exchange across the plasma membrane, and so pH change could impact the differentiation of erythoid lineage cells. The importance of functional AE1 in the regulation of differentiated erythroid cells is supported by the funding that pH is a potent modulator and plays a role in the maintenance of the bone marrow microenvironment and development of erythroid cells (Endo et al, 1994;McAdams et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Functional AE1 mediates the Cl À /HCO 3 À exchange across the plasma membrane, and so pH change could impact the differentiation of erythoid lineage cells. The importance of functional AE1 in the regulation of differentiated erythroid cells is supported by the funding that pH is a potent modulator and plays a role in the maintenance of the bone marrow microenvironment and development of erythroid cells (Endo et al, 1994;McAdams et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…At 22°C, glucose, which is abundantly present in CPDA-1 (2.9 g/dl), is metabolized rapidly into lactate and CO 2 , resulting in a drop in pH. Deviation of culture pH has been shown to affect both the cloning efficiency and differentiation potential of progenitor cells, 36,37 and indeed in separate experiments with mononuclear cells, a pH of 6.8 or lower negatively influenced CFU-GM recovery. Therefore, we hypothesized that either a strong buffer or an alternative to glucose, resulting in less lactate production, should be used.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work demonstrated the importance of pH in Mk maturation and consistently showed that culturing primary Mks at higher pH in the range from 7.2 to 7.6 increased production of high-ploidy ( > 4N) Mks. 9,29 pH also modulates the differentiation of granulocytes, 41,59,60 erythrocytes, 60,61 and BM stromal cells. 62 Hematopoietic stem cells reside close to the bone surface and migrate toward the sinuses during maturation (Fig.…”
Section: Discussionmentioning
confidence: 99%